TASK-BASED LEARNING IN ENGLISH CLASSROOMS - Behruzkhon Yuldoshev Behzod ugli (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Task-Based Learning (TBL) is an innovative approach in English language teaching that focuses on using communicative tasks as the central unit of planning and instruction. It emphasizes meaning over form and encourages learners to use the target language as a tool for authentic communication rather than simply a subject of study. The purpose of this article is to analyze the theoretical foundations, pedagogical principles, and practical applications of task-based learning in English classrooms, highlighting its benefits for language acquisition, motivation, and learner autonomy.